Uji Organoleptik & Karakteristik Fisikokimia Serta Aktivitas Antioksidan Produk Susu Berbasis Kacang Sacha Inchi (Plukenetia volubilis L.) - Nurfadilah M. Kasim; Netty Ino Ischak; Yuszda K. Salimi; Nurhayati Bialangi; La Ode Aman; Erni Mohamad (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to formulate and examine the physicochemical characteristics and antioxidant activity of sacha inchi (Plukenetia volubilis L.) as a plant-based milk. Moreover, this research also aims to conduct organoleptic tests on the products. The sacha inchi milk is formulated with five ratios: SI1 (sacha inchi 1:10 parts water), SI2 (sacha inchi 2:10 parts water), SI3 (sacha inchi 3:10 parts water), SI4 (sacha inchi 4:10 parts water), and SI5 (sacha inchi 5:10 parts water). Organoleptic tests are carried out by assessing the aspects of taste, color and aroma of the product with a score range of 1 (least preferred) - 5 (most preferred). The results of the organoleptic test showed that the most preferred sacha inchi peanut milk formulation was SI5 with a preference level reaching a score of 4.48. The SI5 formulation is more dominantly preferred because it is richer in taste, color and aroma. Then continued with physicochemical testing which includes water content, ash content, fat content, protein content, carbohydrate content, calcium content, pH, and viscosity and IC50 antioxidant activity test using UV-Vis Spectrophotometer instrument. The results of physicochemical tests and IC50 antioxidant activity conducted in this study were respectively: water content (74.10%), ash content (0.65%), fat content (19.15%), protein content (4.29%), carbohydrate content (1.82%), calcium content (0.043%), pH (6.01), viscosity (209 mPa∙S), and IC50 antioxidant activity (429.10 ppm).